The Effect of Learning Module Program on Mothers’ Ability to Adapt to New Foods, Feeding Styles, and Self-efficacy to Their Children with Avoidant Restrictive Food Intake Disorder - Prasetyo, Yoyok Bekti; Dewi, Yulis Setiya; Arifin, Hidayat; Kamel, Amel Dawod (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The education to improve a mother’s knowledge is deemed to be important because it may improve children’s nutritional status. AIM: The aim of this study was to examine the effects of learning module program on the mothers’ ability to adapt to new foods, feeding styles, and self-efficacy to their children with avoidant restrictive food intake disorder (ARFID). METHODS: Quasi-experimental design was used to evaluate the effectiveness of learning module program. Fifteen mothers of experimental group were given four meetings within 4 weeks. Each meeting ran about 50 min. Fifteen mothers of control group were conducted home visit and received twice education about the health principals of feeding children. Both experimental group and control group had pre-test and post-test. The data were analyzed using Chi-square test, Fisher’s exact test, and Mann–Whitney U-test. RESULTS: The participants of the experimental group have shown bigger surge of new foods adaptation (t = –2.973, p < 0.003), feeding style (t = –4.646, p < 0.001), self-efficacy (t = –3.652, p = 0.001) than the control group has. CONCLUSION: The findings indicated that the learning module program was deemed to be effective to improve mothers’ ability to adapt to new foods, feeding styles, and self-efficacy to their children with ARFID.